Quantitation of [5-CH(3)]-(2R, 4'R, 8'R)-α-Tocopherol in Humans(2) - Chuang, Jennifer C. (American Society for Nutrition, 2011)
Half-lives of α-tocopherol in plasma have been reported as 2–3 d, whereas the Elgin Study required >2 y to deplete α-tocopherol, so gaps exist in our quantitative understanding of human α-tocopherol metabolism. Therefore, 6 men and 6 women aged 27 ± 6 y (mean ± SD) ingested 1.81 nmol, 3.70 kBq of [5-(14)CH(3)]-(2R, 4'R, 8'R)-α-tocopherol. The levels of (14)C in blood plasma and washed RBC were monitored frequently from 0 to 460 d while the levels of (14)C in urine and feces were monitored from 0 to 21 d. Total fecal elimination (fecal + metabolic fecal) was 23.24 ± 5.81% of the (14)C dose, so feces over urine was the major route of elimination of the ingested [5-(14)CH(3)]-(2R, 4′R, 8′R)-α-tocopherol, consistent with prior estimates. The half-life of α-tocopherol varied in plasma and RBC according to the duration of study. The minute dose coupled with frequent monitoring over 460 d and 21 d for blood, urine, and feces ensured the [5-(14)CH(3)]-(2R, 4'R, 8'R)-α-tocopherol (the tracer) had the chance to fully mix with the endogenous [5-(14)CH(3)]-(2R, 4'R, 8'R)-α-tocopherol (the tracee). The (14)C levels in neither plasma nor RBC had returned to baseline by d 460, indicating that the t(1/2) of [5-CH(3)]-(2R, 4′R, 8′R)-α-tocopherol in human blood was longer than prior estimates.